Cluster approach to the development of the mechanism of export of agricultural enterprise products - N. R. Suchkova (Управление)
The article studies enterprises of the grain-product subcomplex engaged in the production and sale of grain for both domestic consumption and export. The author studies the cluster approach as a basis for grain export mechanism development, the key element of which is the principle of combining functions of sales, storage, and shipment of products in the transportation and logistics part of the cluster. Achievement of synergetic effect in this case is conditioned by mutually beneficial cooperation of subjects on the investment and innovation basis. The paper summarizes main stages of organizing agricultural exports, each of which presents a list of procedures and composition of the documents used. Based on the conducted research, modern mechanism of export of products (grain) by agricultural enterprises has been presented with the allocation of subjects by stages of the export life cycle depending on the way of its realization (directly, through an intermediary, or as a cluster participant). The example of an export-oriented enterprise in the Saratov region shows clustering effectiveness, which consists in minimizing transaction costs by reducing other implementation costs. The research results can be used when developing programs and proposals to strengthen integration ties between the subjects of agro-industrial complex.